PEDAGOGICAL CONDITIONS OF EDUCATION OF WORLDVIEW CULTURES OF STUDENTS IN EXTRACURRICULAR WORK - M.V. Dolzhenko (Academy of Cognitive and Natural Sciences, 2008)
The article deals with the analysis of the notion "world view culture of a person". The favourable pedagogical conditions for the solution of the problems of the world outlook development within the students of the higher schools are concidered and analysed.